On the problem on periodic solutions of one class of systems of difference equations - Ateiwi, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
The scheme of the Samoilenko numerical-analytic method for finding periodic solutions in the form of a uniformly convergent sequence of periodic functions is applied to one class of difference equations.